Occupational Therapy, Self-Efficacy, Well-Being in Older Adults Living in Residential Care Facilities: A Randomized Clinical Trial - Toledano-González, Abel; Labajos-Manzanares, Teresa; Romero-Ayuso, Dulce María (Frontiers in Psychology, 2018)
Abstract Introduction Choosing the type of treatment approach is as important as the treatment itself, also giving and important value to internal variables in the individual that can determine the evolution of the intervention. The main aim of this study is to determine whether individual and/or group occupational therapy leads to changes in generalized self-efficacy and psychological well-being, and to identify the type of therapy that has the best effects on older adults. Method Prospective, randomized, comparing two treatment groups: individual and group therapy during 6 months. A total sample of 70 patients institutionalized in residential care homes for older adults with a mean age of 85 (SD=4). Assessment was conducted using the General Self-Efficacy Scale and Ryff´s Well-being Scale. For analyze the main dependent variables we used ANOVA for intra-subject and inter-subject factors and Pearson correlation between well-being and self-efficacy by type of treatment. Results Groups were equivalent at baseline. The results show statistically significant differences between the two types of therapy, showing a positive correlation between well-being and self-efficacy, being greater at a group level than at and individual level. At the group level, practically all of variables measured in the participants were increased as shown in the results tables, including a better adaptation and predisposition to work Four participants died while the study was being conducted. Conclusions The clinical trial shows that older people in residential centers achieve an increase in emotional well-being and self-efficacy when they receive occupational therapy group, rather than individual treatment not being significant changes. Treatment group participants reported a positive experience and clinical benefits from training program. The clinical trial was registered in the U.S. National Institutes of Health (ClinicalTrials.gov) with NCT02906306 identifier